Effect of Computer Instructional Technique on Secondary School Students’ Motivation in Chemistry in Anambra State - Nnoli, Juliana Nkiru; Onyekpudoro, Chukwunanu Emmanuel (Education and Development Research, 2026)
The study investigated the effect of computer instructional technique on secondary school students’ motivation in Chemistry in Anambra state. Two research questions were formulated to guide the study and two hypotheses were tested at 0.05 level of significance, guided the study. Quasi-experimental research design was adopted for the study. The population of the study was 241 senior secondary year two (SS2) students who offered Chemistry in Orumba South Local Government Area in Anambra state in the year 2024. A sample of 60 students obtained using simple random sampling (balloting with replacement) was involved in the study. The instruments for data collection were the Motivation Inventory Scale (MIS) and Periodic Table Achievement Test (PTAT), validated by three experts from the Departments of Science Education and Educational Foundations, at Nnamdi Azikiwe University, Awka. The reliability of the instruments was established using Cronbach Alpha for MIS and Kuder-Richardson 20 for PTAT and they yielded coefficient values of 0.86 and 0.82 respectively. Data were generated for the study through the administration of the instruments with the aid of two research assistants. The data obtained were analyzed using Mean and standard deviation, while ANCOVA was used to test the null hypotheses at 0.05 alpha level. The findings of the study revealed that students taught with computer instructional technique were more motivated in learning Chemistry concepts, than those in the control group. The study also revealed that gender had no significant influence on student’s motivation in Chemistry. The study recommended among others that Chemistry teachers should adopt computer instructional technique in Chemistry classrooms, be encouraged through seminars and workshops, and be supported financially to do the same.